Lack of bidirectional association between C-reactive protein and depressive symptoms in middle-aged and older adults: Results from a nationally representative prospective cohort study - Li, Xiaohui; Nie, You; Chang, Biru (Frontiers in Psychology, 2023)
Depression is associated with low levels of quality of life and elevated health burden for middle-aged and older adults in resource-limited settings. Although inflammation plays an etiologic role in the development and progression of depression, the directionality of the inflammation-depression relationship is presently unclear, especially in non-western populations. To examine the inflammation-depression relationship among community-dwelling Chinese middle-aged and older adults. We obtained the dataset from the 2011, 2013, and 2015 waves of the China Health and Retirement Longitudinal Study (CHARLS). Participants were aged 45 years old or above at baseline in 2011 and completed the follow-up survey in 2013 and 2015. Depressive symptoms were measured by the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10) and C-reactive protein (CRP) was tested to reflect individual inflammation levels. Cross-lagged regression analyses were conducted to examine the inflammation-depression relationship. Besides, cross-group analyses were performed to test for model invariance across sexes. Pearson correlations revealed no concurrent correlations between depression and CRP for both 2011 and 2015 (ps>0.05, ranging 0.07 t0 0.36). Cross-lagged regression path analyses revealed that the paths from baseline CRP to depression 2013 (ßstd=-0.01, p=0.80), from baseline CRP to depression 2015 (ßstd=0.02, p=0.47), from baseline depression to CRP 2015 (ßstd=-0.02, p=0.40) and from depression at 2013 to CRP 2015 (ßstd=0.03, p=0.31) were not statistically significant. Additionally, autoregressive model did not vary across sex (△c2=78.75, df=54, p=0.02, △CFI<0.01). We failed to find a bidirectional association between CRP and depressive symptoms in middle-aged and older Chinese populations.